Hand, foot, and mouth disease: A case report - Cabral, Luiz Antonio Guimarães [UNESP]; Almeida, Janete Dias [UNESP]; De Oliveira, Maria Lúcia Coutinho [UNESP]; Meza, Ana Cristina [UNESP] (My University, 1998)
Hand, foot, and mouth disease is a viral infection related to coxsackieviruses A5, A6, A9, and A10, coxsackieviruses B2 and B5, and echovirus 11. It generally affects children, but this article presents a clinical case of a young woman with hand, foot, and mouth disease. Patients with this disease have oral and skin lesions that may be confused with other diseases. The differential diagnosis is very important because both dental and medical professionals may misdiagnose the disease and sometimes prescribe an inappropriate medication.
Keywords: Coxsackievirus infection; Hand, foot, and mouth disease; adult; bullous skin disease; case report; dental care; differential diagnosis; disease transmission; Enterovirus; female; hand disease; hand foot and mouth disease; human; mouth ulcer; pathogenicity; skin disease; Adult; Dental Care for Chronically Ill; Diagnosis, Differential; Female; Foot Dermatoses; Hand Dermatoses; Hand, Foot and Mouth Disease; Humans; Oral Ulcer; Skin Diseases, Vesiculobullous